(-)-Epigallocatechin-3-Gallate Suppresses Hyperexcitability in Rat Primary Nociceptive Neurons Innervating Inflamed Tissues: A Comparison with Lidocaine - Syogo Utugi; Yukito Sashide; Mamoru Takeda (Metabolites, 2025)
Objective: Given the side effects and reduced efficacy of conventional local anesthetics in inflammatory conditions, there is a compelling need for complementary alternative medicine (CAM), particularly those based on phytochemicals. While a previous study showed that in vivo local injection of (-)-epigallocatechin-3-gallate (EGCG) into the peripheral receptive field suppresses the excitability of rat trigeminal ganglion (TG) neurons in the absence of inflammation, the acute effects of EGCG in vivo, especially on TG neurons under inflammatory conditions, are still unknown. We aimed to determine if acute local EGCG administration into inflamed tissue effectively attenuates the excitability of nociceptive TG neurons evoked by mechanical stimulation. Methods: The escape reflex threshold was measured to assess hyperalgesia caused by complete Freund’s adjuvant (CFA)-induced inflammation. To assess neuronal activity, extracellular single-unit recordings were performed on TG neurons in anesthetized CFA-inflamed rats in response to orofacial mechanical stimulation. Results: The mechanical escape threshold was significantly lower in CFA-inflamed rats compared to before CFA injection. EGCG (1–10 mM) reversibly and dose-dependently inhibited the mean firing frequency of TG neurons evoked by both non-noxious and noxious mechanical stimuli (p < 0.05). For comparison, 1% lidocaine (37 mM), a local anesthetic, also caused reversible inhibition of the mean firing frequency in inflamed TG neurons responding to mechanical stimuli. Importantly, 10 mM EGCG produced a significantly greater magnitude of inhibition on TG neuronal discharge frequency than 1% lidocaine (noxious, lidocaine vs. EGCG, 19.7 ± 3.3% vs. 42.3 ± 3.4%, p < 0.05). Conclusions: Local injection of EGCG into inflamed tissue effectively suppresses the excitability of nociceptive primary sensory TG neurons, as indicated by these findings. Significantly, locally administered EGCG exerted a more potent local analgesic action compared to conventional voltage-gated sodium channel blockers. This heightened efficacy originates from EGCG’s ability to inhibit both generator potentials and action potentials directly at nociceptive primary nerve terminals. As a result, EGCG stands out as a compelling candidate for novel analgesic development, holding particular relevance for CAM strategies.